Genesis of Red and Lateritic Forest Soils of West Bengal on Catenary Basis, Part I-Morphological Studies - Das, S. N.; Maiti, T. C.; Banerjee, S. K. (Indian Forester, 1980)
Three catenas comprising of ten soil profiles on different physiographic position were taken for this investigation. This paper deals with only morphological studies (Part I) and physico-chemical and mineralogical studies of soils will follow in later part (Part II). The soils are related to the elements of landscape and the sequence represents as a topodrainage sequence. Microclimate, water table, vegetation, erosion-deposition or a combination of these influence the genesis of soils, fully defining the concept of a Catena. The evidence of desilication from morphological studies reveals that these soils have under gone the process of laterisation. Ten soil profiles of the three catenas were classified according to Soil Taxonomy. All the soils have been classed under Alfisol except in the case of the upland and midland profiles of Catena A and the upland profile of Catena C which may be placed under Entisol.